Data for "The Impact of Negative Mood on Event-Related Potentials When Viewing Pornographic Pictures" - Strahler, Jana; Justus Liebig University Giessen (My University, 2021)
Raw data, analysis syntax for the manuscript "The impact of negative mood on event-related potentials when viewing pornographic pictures"
Keywords: event-related potentials; motivated attention; negative affect; pornography addiction; sexual cue reactivity; ddc:150